Identification of suprascapular nerve as related with omohyoid muscle, brachial plexus and clavicle in supraclavicular fossa for selective suprascapular nerve block - Naraporn Maikong (2020)
© 2020. Objective: The suprascapular nerve block at suprascapular fossa is considered an alternative technique for shoulder surgery. The objective of this study was to determine an anatomy of the SSN in relation with the omohyoid muscle, brachial plexus and clavicle. Materials and Methods: Posterior triangle of neck both sides 44 sides from 24 cadavers (16 men and 8 women, age range 55-80 years). Identify the location of inferior belly of omohyoid muscle, SSN and upper trunk of brachial plexus which crossed under each part of clavicle. Measure the distance between sternal end of clavicle to acromial end of clavicle, medial border of inferior belly of omohyoid muscle, SSN and lateral border of upper trunk of brachial plexus by Vernier caliper. Results: The medial border of inferior belly of omohyoid muscle was equally located at middle or lateral parts of the clavicle. The SSN and lateral border of upper trunk of brachial plexus were located at middle part of the clavicle. Additionally, the SSN was 8.67 ± 4.27 mm medial to the medial border of inferior belly of omohyoid muscle and was 13.21 ± 7.27 mm lateral to the lateral border of upper trunk of brachial plexus. No significant difference on right and left sides. Conclusion: The SSN has a consistent relation with the inferior belly of omohyoid muscle and the upper trunk of brachial plexus which are good landmark for the selective SSN block.